Islamic guidelines for parenting and child upbringing - Karim, Fatimah (Mission Soft Foundation, 2024)
Parenting and child upbringing in Islam is a significant aspect of a Muslim's life, deeply rooted in the principles of Islamic jurisprudence (Fiqh). These guidelines encompass the moral, spiritual, social, and physical aspects of a child's development, ensuring they grow up as balanced and righteous individuals. This article delves into the core principles derived from the Quran, Hadith, and classical Fiqh literature.